From bench to bedside and back: translational cardiovascular interventions in veterinary medicine - Popiel-Dziewierz, Sebastian; Noszczyk-Nowak, Agnieszka; Dziewierz, Artur (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2025)
Veterinary interventional cardiology exemplifies the power of reverse translation in cardiovascular medicine. This review examines how procedures initially tested in animal models, refined in human medicine, and subsequently reintroduced to veterinary practice have completed the translational cycle. We analyze several key interventions – pacemaker implantation, patent ductus arteriosus occlusion, balloon valvuloplasty, radiofrequency ablation, septal defect closure, and mitral valve repair by V-Clamp (a veterinary version of the human MitraClip device) – demonstrating how each has evolved through bidirectional knowledge exchange between human and veterinary medicine. We show how spontaneous disease models in companion animals offer superior translational value compared to induced laboratory models. The development costs for cardiovascular devices ($30–94 million) and high failure rates (> 30%) in human trials create compelling economic incentives for integrating veterinary clinical trials as strategic de-risking investments. We provide comparative pathophysiology for key spontaneous disease models, including canine dilated cardiomyopathy and subaortic stenosis, demonstrating their direct relevance to human cardiovascular research through shared genetic, electrophysiological, and hemodynamic features. Current regulatory frameworks lack clear guidance for incorporating veterinary clinical data into human device submissions, creating uncertainty that impedes innovation. As interventional cardiology advances toward miniaturized, intelligent, and personalized therapies, the One Health approach offers a powerful framework for accelerating innovation while improving outcomes across species.